The short-term load forecasting of power system based on genetic-fuzzy algorithm - Qiao-lin Ding; Xue-hua Pan; Jian-xin Liu (2008 China International Conference on Electricity Distribution, 2008)
The fuzzy system with network structure as the forecasting model, and the improved genetic algorithm is taken to confirm system parameters. A case study of load forecasting in a certain power network shows that the model which is based on this way has a better fitting precision.